Engineering of the low-energy beam transport line in the He⁺ ions linac - Dubniuk, S.N.; Dyachenko, A.F.; Tishkin, S.S.; Zajtsev, B.V. (Вопросы атомной науки и техники, 2021)
The design of a low-energy beam transport line in the helium ions linear accelerator is proposed. For experiments with the low-energy helium ions the vacuum chamber in a transport line is in addition included for an irradiation of investigated materials. The mathematical modeling method investigates coordination variants of an injector beam output emittance with an accelerating structure acceptance with use of electromagnetic quadrupole lenses, electrostatic lenses and the focusing solenoid. It is shown that the optimal variant, ad hoc, is the focusing solenoid application. The calculated value of a current of the helium accelerated ions makes 4.5 mА. Запропоновано схему лінії транспортування низькоенергетичного пучка в лінійному прискорювачі іонів гелію. Для експериментів із низькоенергетичними іонами гелію в лінію транспортування додатково включена вакуумна камера для опромінення досліджуваних матеріалів. Методом математичного моделювання досліджено варіанти узгодження вихідного емітанса пучка інжектора з аксептансом прискорювальної структури з використанням електромагнітних квадрупольних лінз, електростатичних лінз і фокусуючого соленоїда. Показано, що найбільш оптимальним для даного випадку є варіант із застосуванням фокусуючого соленоїда. Розрахункове значення струму прискорених іонів гелію становить 4,5 мА. Предложена схема линии транспортировки низкоэнергетического пучка в линейном ускорителе ионов гелия. Для экспериментов с низкоэнергетическими ионами гелия в линию транспортировки дополнительно включена вакуумная камера для облучения исследуемых материалов. Методом математического моделирования исследованы варианты согласования выходного эмиттанса пучка инжектора с аксептансом ускоряющей структуры с использованием электромагнитных квадрупольных линз, электростатических линз и фокусирующего соленоида. Показано, что наиболее оптимальным для данного случая является вариант с применением фокусирующего соленоида. Расчетное значение тока ускоренных ионов гелия составляет 4,5 мА.